Job or the Becoming-Worm. Biblical-Theological Reflections from a Queer/Cuir/Marica Perspective - Santos-Meza, Anderson Fabián (2026)
This article proposes a biblical-theological rereading of the Book of Job from a queer/cuir/marica perspective, articulated through the notion of becoming-worm as a critical operator. Through a vermicular mode of theologizing, the study destabilizes hegemonic doctrinal frameworks, challenges logics of ontological, moral, and epistemological purity, and reinscribes suffering within contemporary geographies of exclusion, illness, and violence. The analysis integrates contributions from critical hermeneutics, liberation theologies, and aesthetic studies, demonstrating how ambiguity, obscenity, and decomposition configure alternative theological practices oriented toward resistance, survival, and the reimagining of the divine.